2014
DOI: 10.1080/10408398.2011.619283
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Review of Protein Network Regulating Obesity Between Validated Obesity Candidate Genes in the White Adipose Tissue of High-Fat Diet-Induced Obese C57BL/6J Mice

Abstract: Worldwide obesity and related comorbidities are increasing, but identifying new therapeutic targets remains a challenge. A plethora of microarray studies in diet-induced obesity models has provided large datasets of obesity associated genes. In this review, we describe an approach to examine the underlying molecular network regulating obesity, and we discuss interactions between obesity candidate genes. We conducted network analysis on functional protein-protein interactions associated with 25 obesity candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 150 publications
0
16
0
1
Order By: Relevance
“…The present study showed that flavonoid-rich ChrSd supplementation significantly down-regulated the expression of genes related to oxidative stress, innate immune and inflammatory responses; i.e., regulation of nitric-oxide synthase activity (Nostrin and Nos2). In addition, ChrSd supplementation downregulated the expression of genes encoding adipogenic factors such as Gdf3 (Andersson, Korach-Andre, Reissmann, Ibanez, & Bertolino, 2008), Gpd1, Cebpb, Lep (Kim et al, 2014), Tgfb1, Tgfbr1 (Yadav et al, 2011), and Lmna (Lelliott et al, 2002), and genes involved in fatty acid synthesis (Elovl1), while it up-regulated genes for fatty acid β-oxidation (Ppara and Echdc2), leading to reduced HF-induced obesity. This alteration in adipose tissue was accompanied by a significantly lower total body weight and improved HF-induced insulin resistance and glucose intolerance, as compared to the control group.…”
Section: Discussionmentioning
confidence: 98%
“…The present study showed that flavonoid-rich ChrSd supplementation significantly down-regulated the expression of genes related to oxidative stress, innate immune and inflammatory responses; i.e., regulation of nitric-oxide synthase activity (Nostrin and Nos2). In addition, ChrSd supplementation downregulated the expression of genes encoding adipogenic factors such as Gdf3 (Andersson, Korach-Andre, Reissmann, Ibanez, & Bertolino, 2008), Gpd1, Cebpb, Lep (Kim et al, 2014), Tgfb1, Tgfbr1 (Yadav et al, 2011), and Lmna (Lelliott et al, 2002), and genes involved in fatty acid synthesis (Elovl1), while it up-regulated genes for fatty acid β-oxidation (Ppara and Echdc2), leading to reduced HF-induced obesity. This alteration in adipose tissue was accompanied by a significantly lower total body weight and improved HF-induced insulin resistance and glucose intolerance, as compared to the control group.…”
Section: Discussionmentioning
confidence: 98%
“…Network analysis was conducted using the Ingenuity Knowledge base, which is a large repository of biological interactions between proteins, RNAs, genes, isoforms, metabolites, complexes, cells, tissues, drugs and diseases, manually curated by experts based on over 3.58 million published studies. 20 The Ingenuity Knowledge base, includes biological interaction data on 19 600 human and 14 700 mouse genes. For each time-point, molecular networks were constructed of direct physical, transcriptional and enzymatic interactions.…”
Section: Molecular Network Analysismentioning
confidence: 99%
“…A recent paper describing a meta-review of micro-array data on high-fat DIO in C57BL/6J mice found that upregulated genes were associated with fatty acid synthesis, inflammation, signal transduction and transporters, and energy homeostasis [ 22 ]. Down-regulated genes were associated with sterol biosynthesis, insulin sensitivity and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%